(untitled) (Development Service Industry Management, 2025)
The article analyzes the relationship between human capital management (HCM) flexibility and the development of an organization’s strategic human capabilities in a changing competitive environment. The study focuses on the role of strategically-oriented HCM and HCM flexibility in forming competitive advantages through strategic human capabilities. The authors define strategic human capabilities as an essential outcome of human resource management at the organizational level, which directly influences the organization’s performance. Specifically, it is noted that the flexibility of HCM practices is a crucial factor that not only enhances employee performance but also mediates the relationship between strategically-oriented human resource management and the development of an organization’s strategic human capabilities. The strategic importance of personnel, defined by their value in achieving the organization’s strategic goals, positively affects this relationship and strengthens the effectiveness of HCM flexibility in developing employees’ capabilities. Based on research, it is proven that organizations focusing on the development of strategic human capabilities demonstrate higher levels of competitiveness and organizational effectiveness. The study also confirms the importance of strategically-oriented HCM as the foundation for developing strategic capabilities and competitive advantages. It is concluded that to achieve sustainable competitive advantage, organizations must invest in HCM flexibility and foster the development of adaptive HCM systems capable of responding to external environmental changes. The results of the study can be valuable for further academic research and practical implementation in organizations aiming to enhance strategic effectiveness through human capital development.